Transfer of surgical competences in the treatment of intersex disorders in Togo - Gnassingbe K; da Silva-Anoma S; Akakpo-Numado G; Tekou A; Kouame B; Aguehounde C; Coupris L; Galifer R; Aubert D; Revillon Y (Wolters Kluwer Medknow Publications, 2009)
Background: To evaluate the impact of scientific seminar on the sexual ambiguity on patients and paediatric surgeons in French-speaking African countries. Materials and Methods: This was a report of the proceeding of a teaching seminar on intersex management, which was held from December 4 th to 8 th , 2006, in the Paediatric Surgery Department of Tokoin Teaching Hospital and the Surgery Department of "Saint Jean de Dieu" Hospital of Afagnan, Togo. Results: There were 107 participants [five professors of paediatric surgery, 62 African paediatric surgeons (including 15 from African French- speaking countries), and 40 general surgeons]. The workshop involved a two-day theoretical teaching session (aimed at understanding, recognising, and treating the sexual ambiguities), and practical session; during these sessions different intersexes (one case of mixed gonadal dysgenesis, two of female pseudohermaphroditism, and two of male pseudohermaphroditism), were operated free of charge. Participants expressed satisfaction and confidence with regard to the management of intersex after the seminar. Conclusion: This scientific forum allowed possible exchange of competence among the paediatric surgeons with regard to efficient treatment of sexual ambiguities.